2009
DOI: 10.2174/157340309787048059
|View full text |Cite
|
Sign up to set email alerts
|

Patient Radiation Doses in Interventional Cardiology Procedures

Abstract: Interventional cardiology procedures result in substantial patient radiation doses due to prolonged fluoroscopy time and radiographic exposure. The procedures that are most frequently performed are coronary angiography, percutaneous coronary interventions, diagnostic electrophysiology studies and radiofrequency catheter ablation. Patient radiation dose in these procedures can be assessed either by measurements on a series of patients in real clinical practice or measurements using patient-equivalent phantoms. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
62
0
7

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 124 publications
(74 citation statements)
references
References 90 publications
5
62
0
7
Order By: Relevance
“…CA PTCA Pantos [12] Katritsis [29] Toossi [30] Uniyal [4] Bogaert [13] Signorotto [8] mean Effective Dose (mSv) CA PTCA …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CA PTCA Pantos [12] Katritsis [29] Toossi [30] Uniyal [4] Bogaert [13] Signorotto [8] mean Effective Dose (mSv) CA PTCA …”
Section: Discussionmentioning
confidence: 99%
“…However, the potential risk of patient radiation damage must be viewed in the context of the general benefit of these procedures and the likelihood of greater trauma associated with heart surgical interventions and perhaps with imminent death if the intervention was not performed. Radiation dose associated with IC procedures is a complex function of a large number of variables including the X-ray tube voltage (kVp) and the product of tube current and exposure time (mAs), the X-ray field size, the number of projections, focus-skin distance as well as practical skill of the operator [12]. Therefore, for optimizing radiation exposure in such procedures, it is essential to measure patient doses in a given set-up of cardiac catheterization laboratory.…”
Section: Introductionmentioning
confidence: 99%
“…A major difficulty of such an evaluation is that the values of organ doses associated with ICPs are not easily available in the literature. However, as presented by Pantos et al (2009), even for a specific IC procedure, patient doses vary a lot. Organ doses are generally derived from mathematical modelling of the dose-area product (Monte Carlo simulations), inducing another source of approximation.…”
Section: Discussionmentioning
confidence: 99%
“…During these procedures, the organs surrounding the heart are exposed to ionising radiation (Pattee et al, 1993;Harrison et al, 1998;Delichas et al, 2003), in particular the lung and bone marrow. It has been shown that patient radiation doses may markedly vary among the ICPs, but also according to patients, operators or X-ray equipment (Bar et al, 2008;Pantos et al, 2009). There is a current debate about whether the widespread use of X-rays could result in an increased incidence of long-term effects, in particular cancers, in this population; it was estimated that on average, in every 100 000 patients subjected to ICPs, about 80 patients would develop fatal cancer during the next 40 years (Efstathopoulos et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…The K AP values from tables 4 and 5 were used to calculate E, resulting to a range from 0.2 to 48.3 mSv for CA procedures and 1.2 to 33.1 mSv for PCI procedures. Effective doses in bibliography ranged between 0.3 to 15.8 mSv for a CA procedure and 0.9 to 44.7 mSv for a PCI procedure [30]. These wide ranges in patient doses may be attributed to the procedure complexity (due to patient anatomy, physician experience, etc.)…”
Section: Effective Dosementioning
confidence: 99%